IMPACT OF MICROFINANCE ON WOMEN EMPOWERMENT THROUGH POVERTY ALLEVIATION: AN ASSESSMENT OF SOCIO- ECONOMIC CONDITIONS IN CHENNAI CITY OF TAMIL NADU - Sultana, H. Yasmeen; Jamal, M. Abdul; Najaf, Dur-E (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
The empowerment of women is one of the central issues in the process of development of countries all over the world. Poverty is one of the major reasons of womenâs disempowerment. Different micro and macro level strategies are being used by government agencies and NGOs for poverty alleviation of women as a way to empower them. Microfinance has become an important component of development, poverty reduction and economic regeneration strategy around the world. In India, Microfinance programme are implemented through Self Help Groups (SHGs). The SHG is an association of people belonging to similar socio-economic characteristic, residing in same locality. The SHGs are voluntary associations of people formed to attain some common goals. These are groups have similar social identity, heritage, caste or traditional occupations. The present study is analyses the role of microfinance in empowering Muslim women as well as non-Muslim women in a comparative perspective and a comparison between members of SHGs and non-members to gain better insights into the working of SHGs. The concept of microfinance is analysed by using the size of loan received, recovery of loan, and period of loan and the economic, social and knowledge empowerment is used to analyse the empowerment. The results were tabulated by using of logistic regression model. Finally, it is concluded that that microfinance brought knowledge and social empowerment than economic empowerment. Impact of micro finance is appreciable in bringing confidence, courage, skill development and empowerment.